Phase 2a Clinical Trial of Mitochondrial Protection (Elamipretide) During Stent Revascularization in Patients With Atherosclerotic Renal Artery Stenosis. (September 2017) - Saad, Ahmed; Herrmann, Sandra M.S.; Eirin, Alfonso; Ferguson, Christopher M.; Glockner, James F.; Bjarnason, Haraldur; McKusick, Michael A.; Misra, Sanjay; Lerman, Lilach O.; Textor, Stephen C.
Abstract : Background—: Atherosclerotic renal artery stenosis reduces renal blood flow (RBF) and amplifies stenotic kidney hypoxia. Revascularization with percutaneous transluminal renal angioplasty (PTRA) and stenting often fails to recover renal function, possibly because of ischemia/reperfusion injury developing after PTRA. Elamipretide is a mitochondrial-targeted peptide that binds to cardiolipin and stabilizes mitochondrial function. We tested the hypothesis that elamipretide plus PTRA would improve renal function, oxygenation, and RBF in patients with atherosclerotic renal artery stenosis undergoing PTRA. Methods and Results—: Inpatient studies were performed in patients with severe atherosclerotic renal artery stenosis scheduled for PTRA. Patients were treated before and during PTRA with elamipretide (0.05 mg/kg per hour intravenous infusion, n=6) or placebo (n=8). Stenotic kidney cortical/medullary perfusion and RBF were measured using contrast-enhanced multidetector CT, and renal oxygenation by 3-T blood oxygen level−dependent magnetic resonance imaging before and 3 months after PTRA. Age and basal glomerular filtration rate did not differ between groups. Blood oxygen level−dependent imaging demonstrated increased fractional hypoxia 24 hours after angiography and stenting in placebo (+47%) versus elamipretide (−6%). These were reverted to baseline 3 months later. Stenotic kidney RBF rose (202±29–262±115 mL/min; P =0.04) 3 months after PTRA in the elamipretide-treated group only. Over 3 months, systolic blood pressure decreased, and estimated glomerular filtration rate increased ( P =0.003) more in the elamipretide group than in the placebo group ( P =0.11). Conclusions—: Adjunctive elamipretide during PTRA was associated with attenuated postprocedural hypoxia, increased RBF, and improved kidney function in this pilot trial. These data support a role for targeted mitochondrial protection to minimize procedure-associated ischemic injury and to improve outcomes of revascularization for human atherosclerotic renal artery stenosis. Clinical Trial Registration—: URL:https://www.clinicaltrials.gov . Unique identifier: NCT01755858. Abstract : Supplemental Digital Content is available in the text.